ANALISIS PENERAPAN ASAS LANGSUNG, UMUM, BEBAS, RAHASIA, JUJUR, DAN ADIL TERHADAP PEMILIHAN WAKIL BUPATI TULUNGAGUNG SISA MASA JABATAN 2018-2023 - Dwianto, Arditio; Makhali, Imam (Universitas Islam Kadiri, 2024)
This research examines the application of the direct, general, free, confidential, honest and fair principles in the Election of the Deputy Regent of Tulungagung for the Remaining Term of Office for 2018-2023. The purpose of this study is to examine how the application of the direct, general, free, secret, honest and fair principles in the Election of the Deputy Regent of Tulungagung Remaining Term of Office 2018-2023 and how to review the criminal provisions contained in Law Number 10 of 2016 regarding the election process Deputy Regent of Tulungagung. This research method uses normative legal research. The results of this study explain that the application of the direct, general, free, confidential, honest and fair principles is not reflected in the holding of the Tulungagung Deputy Regent Election for the Remaining Term of Office for 2018-2023 due to deviations in the election implementation of these principles. The voting process for the election of the Deputy Regent of Tulungagung Remaining Term of Office for 2018-2023 also violates criminal provisions as stipulated in Article 178B, Article 178C paragraph (2), Article 178G, and Article 178H of Law Number 10 of 2016 due to several actions, namely (1) the act of voting more than once; (2) the act of ordering other people to vote more than once; (3) the act of accompanying voters who do not have physical barriers; and (4) the act of informing other people of the voter's choice.